How the story of the South African experience in the Italian campaign was recorded - and distorted (Historia, 2021)
Despite the best efforts of professional historians attached to the 6th South African Armoured Division, the demands of morale building overwhelmed those of historical accuracy and the true story of the ordinary South African soldier has been left untold. Unsurprisingly, after 67 years individual memories have become distorted, but the cleansing of the national memory began as events were happening. This article explains how the story of the war in Italy was conveyed to the South African public and how propaganda and censorship contributed to the misconceptions which became inculcated in the national consciousness. Contemporary accounts were subjected to censorship and accentuated the positive and post-war literature does little to change these perceptions. Conflicting accounts of the Battle of Chiusi illustrate how language transformed events from a defeat into a triumph of the indomitability of the human spirit. Taboo topics of sexuality, alcohol use, atrocities and battle fatigue are mostly absent from the literature. Conventional wisdom regarding enlistment and the unwillingness to serve is challenged by arguing that almost all formations within the 6th South African Armoured Division, apart from rifle companies, were over-subscribed. An analysis of casualty statistics revealed that the life of an infantryman was indeed precarious, whereas for the ordinary member of the division, death or injury was typically caused by accident.  Nieteenstaande die beste pogings van professionele historici wat aan die 6de Suid-Afrikaanse Pantserdivisie verbonde was, het die eise van moreelbou die eise van historiese akkuraatheid oorskadu. Die ware verhaal van die gewone Suid-Afrikaanse soldaat het dus onvertel gebly. Dit is nie verbasend nie dat individuele herinneringe oor 'n tydperk van 67 jaar verdraai is, maar die "reiniging" van die nasionale geheue het reeds tydens die gebeure self begin. Hierdie artikel verduidelik hoe die verhaal van die oorlog in Italië aan die Suid-Afrikaanse publiek voorgestel is en hoe propaganda en sensuur tot die wanopvattings bygedra het wat in die nasionale bewussyn ingeprent is. Tydgenootlike verslae is aan sensuur onderwerp en het die positiewe beklemtoon, terwyl na-oorlogse literatuur weinig gedoen het om opvattinge te verander. Taboe onderwerpe oor seksualiteit, alkoholmisbruik, wreedhede en gevegsvermoeidheid is meestal afwesig in die literatuur. Konvensionele wysheid rakende indiensneming en die onwilligheid om te dien is nie op die 6de Suid-Afrikaanse Pantserdivisie van toepassing nie. Ongevalle statistieke word ondersoek wat bewys dat sterftes en beserings hoofsaaklik voorgekom het in infanterie-eenhede, hoewel ongelukke vir 25 persent van beserings verantwoordelik was. Weersprekende weergawes van die Slag van Chiusi illustreer hoe taal gebeure kon omvorm van 'n nederlaag tot 'n oorwinning van die ontembaarheid van die menslike gees.
Keywords: Censorship; 6de Suid-Afrikaanse Pantserdivisie; Propaganda; Second World War; Italy; Social memory; 6th South African Armoured Division; Italie; Tweede Wereldoorlog; Sensuur; Sosiale geheue